RARE-30. CASE SERIES OF INTRACRANIAL NON-GERMINOMATOUS GERM CELL TUMOR: A SINGLE INSTITUTION EXPERIENCE. (5th November 2018) - Shah, Nidhi; Walter, Andrew
Abstract: Intracranial non-germinomatous germ cell tumors are a rare, heterogenous group of neoplasms, commonly occurring in the pineal and/or suprasellar regions. The subtypes include yolk sac tumor (YST) or endodermal sinus tumor (EST), embryonal carcinoma (EC), choriocarcinoma (CHC), and mixed malignant subtypes. Diagnosis is usually made without a biopsy, through detection of elevated levels of Alpha-fetoprotein (AFP) and/or beta-human chorionic gonadotropin (βHCG) in the serum and/or cerebrospinal fluid. Three patients with intracranial NGGCT were treated at our institution, using a combination of surgery, chemotherapy, and/or radiation therapy. The clinical presentation of all cases included signs and symptoms of obstructive hydrocephalus. Patient #1 was diagnosed with malignant teratoma at birth via neuroimaging; she died from complications due to surgical resection. Patient #2 was diagnosed with choriocarcinoma of the pituitary gland at age 5 years via elevated AFP in serum and CSF; he was treated with alternating cycles of carboplatin/etoposide and ifosfamide/etoposide, followed by whole ventricle radiation therapy. He is now 28 months off-therapy, without evidence of disease. Patient #3 was diagnosed with choriocarcinoma of the pineal and suprasellar regions at the age 7 years, via elevated beta-HCG in serum and CSF, with evidence of bimodal disease. Treatment included 6 cycles of risk-adapted chemotherapy followed by whole ventricle radiation therapy. Neuroimaging continues to show no evidence of disease with normalization of tumor markers, at 24 months off-therapy. Patients #2 and #3 have residual neuroendocrine and neuropsychological deficits, but remain neurodevelopmentally appropriate. Combination of chemotherapy and radiation therapy is required for optimal prognosis.